2013
DOI: 10.2337/db13-0095
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Loss of IRS1 and IRS2 Causes Heart Failure and Is Controlled by p38α MAPK During Insulin Resistance

Abstract: Cardiac failure is a major cause of death in patients with type 2 diabetes, but the molecular mechanism that links diabetes to heart failure remains unclear. Insulin resistance is a hallmark of type 2 diabetes, and insulin receptor substrates 1 and 2 (IRS1 and IRS2) are the major insulin-signaling components regulating cellular metabolism and survival. To determine the role of IRS1 and IRS2 in the heart and examine whether hyperinsulinemia causes myocardial insulin resistance and cellular dysfunction via IRS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 52 publications
5
161
2
1
Order By: Relevance
“…The beating heart requires a continuous energy supply to maintain its contractile function, and unfavorable energy substrate utilization correlates with the development of cardiomyopathy (21). In the present study, neonatal DEX administration decreased cardiac GLUT4 expression but increased PDK4 expression at the protein level, suggesting reduced cardiac glucose uptake and oxidation.…”
Section: Discussionmentioning
confidence: 45%
“…The beating heart requires a continuous energy supply to maintain its contractile function, and unfavorable energy substrate utilization correlates with the development of cardiomyopathy (21). In the present study, neonatal DEX administration decreased cardiac GLUT4 expression but increased PDK4 expression at the protein level, suggesting reduced cardiac glucose uptake and oxidation.…”
Section: Discussionmentioning
confidence: 45%
“…Dysregulation of IRS1 has been considered a key mechanism of insulin resistance in diabetes mellitus 20. In addition, recent findings have also linked IRS1 to the regulation of mitochondrial function in the heart 21. We therefore assessed changes at the level of IRS1.…”
Section: Resultsmentioning
confidence: 99%
“…Activated IR or IGF-1R directly phosphorylates tyrosine residues on several substrates including IRS-1,-2,-3,-4, Shc, Grb-2-assocated protein (Gab1), Dock1, Cbl and APS adaptor proteins, subsequently providing specific docking sites for other signaling proteins in activating downstream protein kinases (White 2003). Mice lacking both IR and IGF-1-R in the heart displayed similar cardiac phenotype to that of H-DKO mice, in which elimination of PI-3K and Akt activity in cardiomyocytes contributed to cardiac failure and animal death (Laustsen et al 2007, Qi et al 2013. These studies revealed a fundamental mechanism for endogenous kinase activation of PI-3K and Akt that is entirely dependent on IRS-1 and -2 or insulin and IGF-1 in the heart.…”
Section: :3mentioning
confidence: 90%
“…To investigate the role of cardiac insulin signaling, we generated H-DKO mice with heart-specific deletion of both IRS-1 and IRS-2 genes using the Cre/loxP genetic approach. The mice all developed dilated cardiomyopathy and males died of heart failure at the age of 6-9 weeks with cardiac energetic deficiency, mitochondrial dysfunction, myocardial structural damage and contractile functional loss (Qi et al 2013, Riehle et al 2013. These studies revealed novel findings of insulin action in control of cardiac growth, homeostasis and survival.…”
Section: Control Of Cardiac Homeostasis By Irs-1 and Irs-2mentioning
confidence: 94%
See 1 more Smart Citation